2014
DOI: 10.2106/jbjs.m.00655
|View full text |Cite
|
Sign up to set email alerts
|

Intercalary Allograft Reconstructions Following Resection of Primary Bone Tumors

Abstract: We report high complication rates and considerable failure rates for the use of intercalary allografts; complications primarily occurred in the first years after surgery, but some occurred much later after surgery. To reduce the number of failures, we recommend reconsidering the use of allografts for reconstructions of defects that are ≥15 cm, especially in older patients, and applying bridging osteosynthesis with use of plate fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
128
5
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(159 citation statements)
references
References 27 publications
14
128
5
4
Order By: Relevance
“…The intercalary tumour resection results in a segmental bone defect and can represent a challenging reconstructive problem. The surgical options for reconstructing these defects include biologic reconstructions such as an allograft [1][2][3], nonvascularised or vascularised fibular grafts [4,5], autogenous extracorporeally-treated bone [6][7][8][9][10], bone transport [11,12] or the combination of an allograft with vascularised fibular grafts. Nonbiologic reconstructions, on the other hand, use intercalary endoprostheses [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The intercalary tumour resection results in a segmental bone defect and can represent a challenging reconstructive problem. The surgical options for reconstructing these defects include biologic reconstructions such as an allograft [1][2][3], nonvascularised or vascularised fibular grafts [4,5], autogenous extracorporeally-treated bone [6][7][8][9][10], bone transport [11,12] or the combination of an allograft with vascularised fibular grafts. Nonbiologic reconstructions, on the other hand, use intercalary endoprostheses [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Although fractures were common in our series, the intramedullary free fibula allowed the fractures to heal with ORIF or nonoperatively, which could not occur in an allograft alone. Infection has been shown to occur in 5% to 18% of allografts [2,8,33,36,43]. Although a majority of our patients in our series were undergoing chemotherapy, which has been shown to increase the risk of infection [11], we did not have any postoperative infectious complications.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have shown that the outer surface of the allografts becomes populated with living cells; however, the inner allograft remains acellular [4,6,22]. Because the allograft is acellular and lacks a blood supply, when complications such as fracture and infection occur, the body is unable to heal the injury like native vascularized bone [5,7,8,13,17,26,27,33,34,36]. In our patient cohort, nonunions occurred in six patients.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Traditionally, such intercalary reconstructions are considered among the better allograft reconstruction options. However, a recent review by Bus and colleagues [2] found an overall complication rate of 76% with this type of reconstruction, particularly when the graft segments exceeded 15 cm in length. Similarly, a recent study by Schuh and colleagues [7] found a 65% revision/reoperation rate for autologous fibula reconstructions (both vascularized and nonvascularized) and a 25% nonunion rate.…”
mentioning
confidence: 99%